Prevalence, characterization, and genotypic analysis of Escherichia coli O157:H7/NM from selected beef exporting abattoirs of Argentina - Masana, Marcelo (2010)
Fil: Mosana, M. O. Instituto Tecnología de Alimentos, Centro de Investigación de Agroindustria, Instituto Nacional de Tecnología Agropecuaria, INTA, CC. 77, B1708WAB Morón, Pcia. de Buenos Aires; Argentina.